2018
DOI: 10.3390/su10082643
|View full text |Cite
|
Sign up to set email alerts
|

How Social Entrepreneurs Affect Performance of Social Enterprises in Korea: The Mediating Effect of Innovativeness

Abstract: Schumpeter argued that entrepreneurship brings about creative destruction in capitalist economies. South Korea enacted the Social Enterprise Promotion Act in 2007 to promote corporate social enterprise. However, despite government support, social enterprises in Korea are not successful, especially in social and economic performance, which is defined as the social and economic value that social enterprises should pursue. A questionnaire survey was conducted among 100 social entrepreneurs, and the structural equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 47 publications
0
34
2
2
Order By: Relevance
“…Vigorous marketing capability supports the performance of commercial activities more efficiently because it allows the company to cope with market changes and its complexities [35]. In social enterprises, innovation is necessary to not only be better than their competitors, but to also satisfy social needs differently from profit enterprises [54,56] and with greater social impact [62]. In addition, whereas marketing capability had a significant indirect effect on social value creation through social innovation, the effect on economic value creation was not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vigorous marketing capability supports the performance of commercial activities more efficiently because it allows the company to cope with market changes and its complexities [35]. In social enterprises, innovation is necessary to not only be better than their competitors, but to also satisfy social needs differently from profit enterprises [54,56] and with greater social impact [62]. In addition, whereas marketing capability had a significant indirect effect on social value creation through social innovation, the effect on economic value creation was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…From RBT, social innovation is developed by applying a combination of resources available, creating new routines, or new ways of doing things [55]. However, it is necessary to creatively combine those resources in new ways to solve communal problems [56], given that social enterprises that lack innovation have a lower probability of surviving in the long term [57].…”
Section: Introductionmentioning
confidence: 99%
“…The factors affecting SEP presented in the previous studies vary widely from study to study: the management capabilities of social entrepreneurs, leadership of social entrepreneurs, social entrepreneurship, networking with various stakeholders, organizational structure, governance, strategy, social support and cooperation, market competitiveness, balance as a hybrid organization, solidarity, values, and missions. While various factors are suggested, four major factors affect SEP: human, institutional, organizational, and environmental factors [34]. The leadership and management capacity of social entrepreneurs, social entrepreneurship, and employee competence are human factors [35][36][37].…”
Section: The Performance Of Social Enterprises and The Factors Affectmentioning
confidence: 99%
“…However, in the subjective measurement of individual values, characteristics, and organizational performance, there are differences in the measurement level of variables. In other words, many studies identified the organizational and individual-level characteristics through subjective questionnaire surveys, and the survey respondents understood business situations and company environments well [30][31][32][33][34]. According to Liu et al, who analyzed the relationship between marketing capabilities and the social-economic SEP, subjective ratings to measure financial and social performance are a reliable and valid assessment because managerial decisions and actions are somewhat accurately perceived by the chief executives of companies.…”
Section: Research Modelmentioning
confidence: 99%
See 1 more Smart Citation